Optimalisasi Pemanfaatan Generatif AI dalam Pemberdayaan Kreativitas Musik Penyandang Disabilitas - Fatmariani; Eka Prasetya Adhy Sugara; Azalia Mawarindani Indra (Forum Kerjasama Pendidikan Tinggi, 2025)
Artificial Intelligence (AI) technology, especially Generative AI, opens up new opportunities in the fields of art and creativity, including in digital music production. This community service activity aims to empower people with disabilities through training in the use of Generative AI in the digital music creation process. The partner in this activity is a community of people with disabilities in the city of Palembang, namely the Sharing Disability Indonesia Foundation, who have an interest in music, but are physically and sensorily limited. The implementation method is carried out through a participatory approach with the following stages: technology socialization, training in the use of generative AI platforms such as Suno AI, and assistance in the process of producing digital music works. Evaluation is carried out through interviews and assessments of the quality of the musical works produced by participants. The results of this activity show that participants are able to use Generative AI independently to create original music, and experience increased self-confidence and creative expression. This community service proves that technology can bridge the access gap and become an inclusive tool that supports the empowerment of groups with disabilities in the world of art and technology. AI literacy is an important aspect that must be instilled from an early age, not only for people with disabilities but also the general public, so that they can understand, utilize, and adapt critically and creatively to technological advances. Based on the results of the questionnaire, the participants were in the 68-30% interval, meaning that this community service activity had a positive impact on increasing self-confidence and creativity for people with disabilities.